Unilateral or bilateral irradiation in cervical lymph node metastases of unknown primary? A retrospective cohort study. (April 2019) - Pflumio, Carole; Troussier, Idriss; Sun, Xu Shan; Salleron, Julia; Petit, Claire; Caubet, Matthieu; Beddok, Arnaud; Calugaru, Valentin; Servagi-Vernat, Stéphanie; Castelli, Joël; Miroir, Jessica; Krengli, Marco; et al.
Abstract: Introduction: Patients with cervical lymphadenopathy of unknown primary carcinoma (CUP) usually undergo neck dissection and irradiation. There is an ongoing controversy regarding the extent of nodal and mucosal volumes to be irradiated. We assessed outcomes after bilateral or unilateral nodal irradiation. Methods: This retrospective multicentre study included patients with CUP and squamous cellular carcinoma who underwent radiotherapy (RT) between 2000 and 2015. Results: Of 350 patients, 74.5% had unilateral disease and 25.5% had bilateral disease. Of 297 patients with available data on disease and irradiation sides, 61 (20.5%) patients had unilateral disease and unilateral irradiation, 155 (52.2%), unilateral disease and bilateral irradiation and 81 (27.3%), bilateral disease and bilateral irradiation. Thirty-four (9.7%) and 217 (62.0%) patients received neoadjuvant and/or concomitant chemotherapy, respectively. Median follow-up was 37 months. Three-year local, regional, locoregional failure rates and CUP-specific survival were 5.6%, 11.7%, 15.0% and 84.7%, respectively. In patients with unilateral disease, the 3-year cumulative incidence of regional/local relapse was 7.7%/4.3% after bilateral irradiation versus 16.9%/11.1% after unilateral irradiation (hazard ratio = 0.56/0.61, p = 0.17/0.32). The cumulative incidence of CUP-specific deaths was 9.2% after bilateral irradiation and 15.5% after unilateral irradiation (p = 0.92). In multivariate analysis, mucosal irradiation was associated with better local control, whereas no neck dissection, ≥N2b and interruption of RT for more than 4 days were associated with poorer regional control. Toxicity was higher after bilateral irradiation (p < 0.05). No positron-emission tomography–computed tomography, largest node diameter, ≥N2b, neoadjuvant chemotherapy and interruption of RT were associated with poorer cause-specific survival. Conclusion: Bilateral nodal irradiation yielded non-significant better nodal and mucosal control rates but was associated with higher rates of severe toxicity. Highlights: Our study suggests that bilateral neck irradiation might yield better outcomes. Mucosal irradiation yielded better local control. Severe toxicities with bilateral 3D irradiation could be reduced with IMRT. Unilateral elective irradiation cannot yet be considered the standard treatment.